Equalization and beamforming proposals for modern communication systems - Sousa, Tiago Fernando Barbosa de (2019)
This work aims to present new proposals for equalization and beamforming associated with modern digital communication systems. Three proposals are presented in which the first is characterized by an innovative neural equalizer structure called here the Butterfly Neural Equalizer (NE-Butterfly). The NE-Butterfly can be applied to linear and nonlinear intensity-modulated and direct-detection (IM-DD) problems. The second proposal is characterized by an adaptive beamforming scheme applied to Orthogonal FrequencyDivision Multiplexing (OFDM) systems. The OFDM technique and variants are being used in various communication systems such as LTE, digital TV, and others. Finally, the third proposal presents a neural beamforming structure called Butterfly Neural Beamforming (NB-Butterfly) that can be applied to several communication systems. Results associated with the three proposals are presented and show the feasibility of the techniques in several channel scenarios and digital modulation schemes.